Electrically Responsive Shape Memory Composites Using Silver Plated Chopped Carbon Fiber - Wang, Yongkun; Chen, Zhenhong; Niu, Jiahao; Shi, Yang; Zhao, Jiangpeng; Ye, Junjie; Tian, Wenchao (Frontiers in Chemistry, 2020)
High electrical and thermal conductivity are beneficial to the shape recovery performance of electroactive shape memory polymer composites. In this work, the chopped carbon fiber (CCF) was processed into silver plated chopped carbon fiber (Ag/CCF), and the Ag/CCF was filled into hydrogenated bisphenol A epoxy (H-EP) resin to fabricate the electro-induced shape memory polymer composites. The Ag/CCF/H-EP composites show good electrical and thermal conductivity compared to the CCF/H-EP composites. When the content of Ag/CCF reaches 1.8 wt%, the e Ag/CCF/H-EP composites reach the threshold of thermal conductivity, electrical conductivity and percolation. The thermal conductivity of H-EP composite with 5.4 wt% Ag/CCF is 2.33 W/(m·K), which is 2.6 times and 12 times of that of CCF/H-EP composite and H-EP matrix, respectively. When the content of Ag/CCF reaches 7.2 wt%, the volume resistivity of Ag/CCF/H-EP composites decrease from 1.69 × 1016 Ω·to 9.51 × 103 Ω cm, and surface resistivity from 6.91 × 1015 Ω to 6.19 × 102 Ω, respectively. And the Ag/CCF/H-EP composites show good mechanical properties and dynamic thermomechanical properties. When the content of Ag/CCF is more than 1.8 wt%, the Ag/CCF/H-EP composites exhibit excellent electroactive shape memory performance, and the shape recovery rate of the composites is more than 92%.